Alizarin Red-S Protocol for Skeletal Staining during Fetal Period in Rabbit - Reda Mohamed (Academia Anatomica International, 2017)
Background: The main purpose of this study was to give detailed information on the staining protocol of Alizarin Red-S to detect the normal and abnormal skeleton of rabbit fetus. Methods: Eleven (9 females and 2 males) of adult rabbit weighing 3-3.5 kg were used. The female rabbits were left with buck to become pregnant then were classified into a treatment and a control group. The former group received oral doses of 400mg/kg of sodium valproate for 15 days starting from the 6th day after mating until 20th day of pregnancy, while the second received water in the same period. The pregnant rabbit was slaughtered at the 29th day of pregnancy. The live rabbit fetuses were collected. The staining protocol included fixation, dehydration, clearing, staining and preservation. The fetuses were examined under dissecting microscope and photos were taken for documentation. Results: The staining protocol made the rabbit fetuses to be clear enough to see their skeleton through the surrounding tissue. The axial skeleton including skull with mandible, vertebral column, ribs and sternum and the appendicular skeleton including the bones of the fore-and hindlimbs took the stain and became red in color. The macroscopic skeletal disorders of the fetuses of the treatment group were observed. The ossification centres were assessed. Conclusion: This protocol which depended on fixation by 95% ethanol, clearing by 1% potassium hydroxide and staining by 0.001 % Alizarin Red-S was effective in detecting normal and abnormal fetal skeletal morphology.